THE CHOICE OF FINANCIAL PERFORMANCE MEASURES AS ONE OF THE MOST CRITICAL CHALLENGES FACING CORPORATION - Gamsakhurdia, Tamar; Maisuradze, Ketevan (European Scientific Journal, ESJ, 2014)
The value-based measures are discussedby focusing on their measurement logic: The most important value-based measures are: economic value added (EVA), the cash flow return on investment (CFROI), the shareholder value added (SVA), the economic margin (EM) and the cash flow value added (CVA).The aim of this work is the collection and compilation materials about the Value Based Management (VBM) approach. Although an integral part of VBM-approach measures the value of the company, it fundamentally differs from traditional methods of the business evaluation, most of which give a "point" result and are isolated from management context and are snatched out of the ultimate goal and donot assume its monitoring.